Neurological complications of coronary artery bypass graft surgery: six month follow-up study. - Shaw, P J (1986)
As part of a major prospective study of the neurological complications of coronary artery bypass graft surgery patients were reviewed over six months to determine the clinical course and functional impact of early postoperative complications. One hundred and ninety one out of 312 (61%) patients had developed early postoperative disorders. At six months 165 of the 191 patients with early neurological complications were reviewed. Of the 165, 85 still had detectable neurological signs, but these were often minor and of little functional importance. Only 10 patients had neurological disability at six months, and this was major in only four patients, all of whom had suffered major perioperative stroke. No patient with non-disabling neurological complications in hospital became functionally impaired on returning home. Neurological disorders are not a major cause of failure to return to work by six months after coronary artery bypass surgery. Of 139 patients who were of working age and had not returned to work by six months, only four were prevented by neurological injury related to surgery. The long term prognosis for early neurological disorders after coronary artery bypass surgery is usually favourable, except in those patients who have sustained major perioperative stroke.